(untitled) (Research, Society and Development, 2022)
Objective: to evaluate pain symptoms in patients after endodontic treatment of teeth with pulp necrosis under irrigation with 2.5% or 5.25% sodium hypochlorite. Methods: 50 single-rooted maxillary anterior teeth were divided into two groups (n=25). Group HS2: teeth with pulp necrosis rinsed with 2.5% sodium hypochlorite, Group HS5: teeth with pulp necrosis rinsed with 5.25% sodium hypochlorite. All canals were instrumented with Reciproc R25 or R40 or R50 files, depending on the initial diameter, according to the manufacturer’s instructions, and rinsed with 10 mL of solution in each third. At the end, the Easy Clean tip was used, performing 03 cycles of 20s each with 1 mL of 17% EDTA, then 2 mL of 2.5% NaOCl for group HS2 and 5.25% for group HS5, shaking for 3 cycles of 20s. The canals were dried and filled using the single cone technique with AH Plus endodontic cement and sealed with provisional material and glass ionomer. After treatment, patients answered a questionnaire at 24h, 48h, 72h and 07 days post-treatment using the VAS pain scale, which ranks pain intensity from 0 to 10. Data were analyzed using the Biotest 5.0 program and subjected to the Shapiro-Wilk normality test. The sample showed non-parametric behavior and the Kruskal-Walis test was used with a significance level of 5%. Results: There was no statistically significant difference regarding postoperative pain in the scores of VAS scale at 24h, 48h, 72h and 7 days after treatment with sodium hypochlorite at 2.5% and 5.25% (p > 0.05). Pain was mild in both groups. Conclusion: We conclude that 2.5% and 5.25% sodium hypochlorite solutions did not affect the pain level after endodontic treatments.